Online reference & tutorial for microprocessor subject / Velan Ramalingam - Velan, Ramalingam (2003)
This project takes form as a web page which provides microprocessor- related information and news that caters all kinds of users , from novice to expert users. The site content will include news features, opinion polls and discussion boards. This project was proposed in response to the fact that technical site ( such as hardware/software sites) RARELY cater all kind of users, which leaves the users. in the dark when it comes to finding/viewing technical information or to find information that introduces to users to technical topics that helps them understand the site content better. The Online Student Reference & Tutorial of Microprocessor subject project is an initiative towards gearing the society to consider and accept e-learning as the norm. This project is an online based learning system , concentrating on microprocessor related subjects, which will include various audio and visual entities to allow the user a better understanding and grasp of the subject involved. Even though it is designed to suit the requirement and syllabus covered by the Computer Science and Information Technology Faculty of University Malaya, for it's students, it is also adequate to be used by anyone who with to learn the subject independently. In other words, even though the system is created with faculty students in mind, it is still suitable for public consumption.